Emotional intelligence as a strategy to strengthen resilience - Karinel Patiño Briones, Geomara; Fernando Pazmiño Campuzano, Marcos; María San Andrés Laz, Esthela (International Journal of Psychosocial Rehabilitation, 2020)
With the arrival of multiple intelligences and specifically the contribution of Goleman on emotional intelligence, this opens a door to the analysis of the importance of the development of this ability or skill, allowing the human being to develop the ability to face problems, giving way to strengthening resilience, which is presented as the ability to recognize the feelings of oneself and others. This is a topic that is investigated as part of personal recovery from misfortunes, reaching a degree of learning of emotions. The objective of this work is to analyze the contribution of Daniel Goleman on emotional intelligence and its relationship with resilience at different times and from thinkers in the field of scientific research. This bibliographic review was developed, analyzing degree theses, doctorates, and scientific articles from the last few years, in addition to the information from scientific texts in the development of conceptualizations. The analytical and deductive methods were used to make an exhaustive analysis of the information, arguing the main ideas for the development of this section, reaching the convergence of opinions in the development of the discussion, which leads to the conclusions in which both variables contribute to the improvement of the educational process.